A review of adverse effects of damping in seismic isolation. - Politopoulos, Ioannis
In this paper the question of possible adverse effects of damping in seismic isolation because of higher mode response is investigated by means of simple models with a few degrees of freedom (DOF). In particular the second mode response of a 2 DOF system is examined in detail for both viscous and hysteretic (e.g. friction or elastoplastic) damping devices. Qualitative and approximate quantitative estimates are obtained by neglecting the influence of the modal coupling terms, due to viscous damping or friction forces, on the first mode response. It is shown that additional viscous damping has a diminishing effect on base displacement, storey shear force and floor spectra values in the vicinity of the first mode resonance. However, a significant amplification of the floor spectra values near the higher mode frequencies may occur. In accordance with the results of previous works, compared with the viscous damping case, hysteretic damping amplifies moderately the first storey shear force and significantly the upper storeys shear force. It also results, in a much more pronounced amplification of the floor spectral values than viscous damping, in the vicinity of the higher eigenfrequencies. However, the higher modes' response is milder if a realistic velocity dependence of the friction coefficient is taken into account.
Keywords: Seismic isolation; Damping; Friction; Floor spectra